La problemática ambiental como hilo conductor de las prácticas experimentales en las aulas de Ciencias Naturales de secundaria (2019)
This paper presents the results of an experience in rural education. A sequence of classroom was designed, taking as a starting point environmental issues which are harmful to the surroundings of an educational institution located in a peasant area, and its students’ appropriation of the ancestral and day-to-day wisdom. The action research carried out aimed at identifying the existing relationships between the paramuno ecosystem environmental reality, the peasant ancestral wisdom and the school community’s thinking. This research was developed within the Cooperative and Collaborative Learning framework and from a qualitative approach. The use of direct observation, interviews, the dialog of knowledge’s, and diagnostic tests disclosed information concerning the students’ knowledge about their ecosystem. Based on the analysis of the information obtained, field and laboratory activities were undertaken, allowing to transform the traditional teaching practices. This experience shows it is possible to promote situated environmental education in rural contexts as a pertinent approach to the teaching-learning processes in the Natural Sciences.